2018
DOI: 10.1111/caim.12287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ethical leadership on employee social innovation tendency in social enterprises: Mediating role of perceived social capital

Abstract: Although social innovation has gained prominence in policy, academic, and practitioner debates, there remains a lack of understanding of how leader aspects such as behavior and ethics contribute to fostering social innovation among employees in the social enterprise, owing primarily to a dearth of empirical research on this subject. The goal of this study is to empirically examine the effect of ethical leadership on the social innovation tendency among employees in social enterprises; also, employees' perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 117 publications
(230 reference statements)
0
31
0
2
Order By: Relevance
“…The respondents responded to items on a five point Likert scale (1 = never to 5 = every time) with 0.96 Cronbach’s alpha value. This scale is also validated by the existing research; for instance Ofori [ 66 ], and Pasricha and Rao [ 67 ] found a Cronbach’s alpha value of 0.92 and 0.94, respectively. Leaders’ pro-environmental attitude was measured on a 15-item five point Likert type scale (1 = strongly disagree, 5 = strongly agree) [ 68 ].…”
Section: Methodsmentioning
confidence: 69%
“…The respondents responded to items on a five point Likert scale (1 = never to 5 = every time) with 0.96 Cronbach’s alpha value. This scale is also validated by the existing research; for instance Ofori [ 66 ], and Pasricha and Rao [ 67 ] found a Cronbach’s alpha value of 0.92 and 0.94, respectively. Leaders’ pro-environmental attitude was measured on a 15-item five point Likert type scale (1 = strongly disagree, 5 = strongly agree) [ 68 ].…”
Section: Methodsmentioning
confidence: 69%
“…Research on social innovation has been growing (Adams & Hess, ; Cajaiba‐Santana, ; Choi & Majumdar, ; Pasricha & Rao, ) and highlights challenges for policy and management practice (van der Have & Rubalcaba, ). Increasing stakeholder expectations with respect to philanthropic and community investment have led businesses to rethink their roles and their social agendas through social innovation to develop innovative solutions to serve social needs (Herman & Renz, ; Kanter & Summers, ; Mirvis, Herrera, Googins, & Albareda, ; Mulgan, ; Pasricha & Rao, ). Social innovation generally implies a normative stance with the goal of creating something positive for society (MacGregor & Fontrodona, ; Osburg, ).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Third, this study contributes to the integration of social identity theory and leadership literature , by illustrating that empowering and fair leaders are more effective in influencing bricolage when individuals are highly identified. While empowering leadership and interactional justice provide the resources (Shaw, Wild, & Colquitt, 2003;Zhang & Bartol, 2010) As analyzed in the theoretical background, extant research has focused on understanding how leadership affects creativity and innovation, highlighting in particular the positive role of the empowering, transformational aspects of leadership (Byrne et al, 2009;Chong & Ma, 2010;Kim, 2019), as well as starting to focus on a more ethical dimension of the supervisor-coworker relationship to favor innovation (Pasricha & Rao, 2018). The present study builds on this research to illustrate how autonomy, trust, cooperation, and fairness should be combined in order to understand bricolage.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the first stream of research, previous studies have analyzed, for instance, how entrepreneurial leadership (Chen, 2007) in new, high-tech ventures stimulates entrepreneurial team members' creativity. In addition, another study investigated how ethical leadership is associated with social innovation (Pasricha & Rao, 2018), using data collected from 189 employees associated with a variety of social enterprises. Finally, in their study on leaders' emotional intelligence and employees' creativity, Rego et al (2007) When we look at creative and innovative behavior more broadly, it becomes evident that extant studies have tended to focus on the dimensions of trust, autonomy, and support in the supervisorcoworker relationship, with the aim of understanding how leadership might influence innovative behavior.…”
Section: Leadership Identification and Bricolagementioning
confidence: 99%
See 1 more Smart Citation